OLM interneurons differentially modulate CA3 and entorhinal inputs to hippocampal CA1 neurons - Leão, Richardson N (2012)
The vast diversity of GABAergic interneurons is believed to endow hippocampal microcircuits with the required flexibility for memory encoding and retrieval. However, dissection of the functional roles of defined interneuron types have been hampered by the lack of cell specific tools. Here we report a precise molecular marker for a population of hippocampal GABAergic interneurons known as oriens lacunosum-moleculare (OLM) cells. By combining novel transgenic mice and optogenetic tools, we demonstrate that OLM cells have a key role in gating the information flow in CA1, facilitating the transmission of intrahippocampal information (from CA3) while reducing the influence of extrahippocampal inputs (from the entorhinal cortex). We further demonstrate that OLM cells are interconnected by gap junctions, receive direct cholinergic inputs from subcortical afferents, and account for the effect of nicotine on synaptic plasticity of the Schaffer collateral pathway. Our results suggest that acetylcholine acting through OLM cells can control the mnemonic processes executed by the hippocampus.